Endosonographic evaluation of the mediastinum through the i-gel O2 supraglottic airway device. Issue 1 (February 2021) - Piccioni, Federico; Codazzi, Daniela; Paleari, Maria C.; Previtali, Paola; Delconte, Gabriele; Fumagalli, Luca; Manzi, Renato; Faustini, Marco; Persiani, Laura; Rizzi, Maurilia; Sodi, Federico; Masci, Enzo
Introduction: Endobronchial ultrasound (EBUS) is an endoscopic diagnostic procedure combining flexible fibrobronchoscopy with ultrasound techniques; it allows transbronchial needle aspiration biopsy for the diagnosis and staging of mediastinal masses. We present our preliminary experience with the use of the i-gel O2 supraglottic airway device for management of EBUS procedures. Methods: An observational study on 39 patients who underwent EBUS under general anesthesia was performed. Airways were managed with i-gel O2 by anesthesiologists unfamiliar with it. Data collected included patient characteristics, i-gel O2 positioning, mechanical ventilation, procedure, and complications occurring during and after the EBUS. Results: The i-gel airway was successfully positioned during the first attempt in 34/39 cases (87.2%). No failed positioning was recorded. The EBUS scope easily passed through the i-gel in all patients and in 14 (35.6%) cases it was also inserted through the esophagus allowing the examination or fine needle aspiration of paraesophageal lymph nodes. In one case, during the EBUS procedure, the i-gel was dislocated but easily put in place again. During EBUS, air leakages were significant in 2 cases (5.1%) and minimal in 14 cases (35.9%). A brief self-solved laryngospasm and a bronchospasm during bronchoscopy were recorded. After recovery, no patients had dysphagia; mild odynophagia and pharyngodinia were referred by 2 (5.1%) and 12 (30.1%) patients, respectively. Conclusions: The i-gel O2 airway is easy to position and manage even for anesthesiologists unfamiliar with it. This supraglottic airway device is suitable for a complete endosonographic evaluation of the mediastinum.